Assessing in vitro tug-back effect on apical seal - A. Sadeghin; F. Farhadian (Tehran University of Medical Sciences, 1998)
There is lack of consensus among endodontic specialists about the necessity of tug back. In this regard, we designed a study in which 44 single rooted teeth with closed apex were selected and filed up to file #50. The teeth were obturated with lateral condensation method while in half of them there was not any tug back and in the other half tug back was achieved. Apical leakage was assessed by color infiltartion via microscope. The obtained results showed significantly lower infiltration in tug back group which leads to a direct relation between tug back and color infiltration although due to statistical analysis, this relationship was not reliable and needs further proofs.